Arrhythmia in an athlete diagnosed by smartphone electrocardiogram: a case report. Issue 5 (24th May 2021) - Phillips, Daniel; O'Callaghan, Peter; Zaidi, Abbas
Abstract: Background: This is the first case report demonstrating the use of a smartphone device, enabling the diagnosis of an arrhythmia in the sports cardiology literature. Case summary: A 17-year-old semi-professional rugby player presented with recurrent episodes of palpitations terminated by vagal manoeuvres. The rugby player's resting 12-lead electrocardiogram (ECG), echocardiogram, and exercise stress test were normal. Due to his suggestive history and an ECG trace from a smartphone device, demonstrating a narrow complex tachycardia, an electrophysiological study was arranged. The study demonstrated a slow-fast atrioventricular nodal re-entrant tachycardia which was successfully ablated. Discussion: The ambulatory use of a smartphone ECG device assisted in the timely diagnosis and management of an undiagnosed paroxysmal arrhythmia in a rugby player. This resulted in an expedited return to play.